Mechanically Tailored Agarose Hydrogels through Molecular Alloying with β‐Sheet Polysaccharides. Issue 2 (22nd September 2014) - Forget, Aurelien; Pique, Raphaelle‐Anne; Ahmadi, Vincent; Lüdeke, Steffen; Shastri, V. Prasad; Frey, H.; Mecking, S.
<x xml:space="preserve">Abstract</x> There is mounting evidence that the mechanical property of tissues provides important cues that control cell fate. However, implementation of hydrogels with tunable physicochemical properties is limited due to the challenges associated with crosslinking chemistries. It has been recently shown that mechanically well‐defined injectable polysaccharide hydrogels can be engineered by switching their secondary structure from an α‐helix to a β‐sheet. Based on these findings, a new concept is presented to tailor the mechanical properties of agarose hydrogels via the blending with the β‐sheet‐rich carboxylated derivative. Using this simple strategy, gels with predictable roughness, fiber organization, and shear modulus ranging from 0.1 to 100 kPa can be formulated. Hydrogels whose mechanical properties can be precisely tailored in vivo without the recourse for chemical reactions are expected to play an important role in implementing mechanobiology paradigms in de novo tissue engineering. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>